METHODS OF FORMATION OF ECONOMIC TERMS IN ENGLISH AND THE PROCESS OF ACQUISITION - Kutliyeva Mukhayyo Gulomovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The practical result of this work is to observe how the emergence and quantitative accumulation of economic vocabulary units in English occurs, in which periods and for what reasons quantitative changes in it turn into qualitative changes - systematic generalization of scientific terms , creating a system of economic terminology, creating a dictionary of economic terms, interpreting explanations of economic terms.